Age, but not hand preference, is related to personality traits in common marmosets (Callithrix jacchus). Issue 10 (19th October 2022) - Masilkova, Michaela; Šlipogor, Vedrana; Lima Marques Silva, Guilherme Henrique; Hadová, Magdaléna; Lhota, Stanislav; Bugnyar, Thomas; Konečná, Martina
Abstract : The proximate mechanisms underlying animal personalities, i.e. consistent inter-individual differences in behaviour, are a matter of discussion. Brain lateralization, expressed as the preferred use of the contralateral limb, has been suggested as one of these mechanisms. In this study, we measured a proxy of brain lateralization in captive common marmosets ( N = 28) by testing hand preference in a simple food-reaching task and evaluated personality by coding a wide range of behaviours observed in daily situations. We explored the links between personality and both direction and strength of hand preference, as well as age and sex, using linear models. Principal component analysis revealed that the stable behavioural variables were organized in three personality dimensions: Agreeableness, Extraversion and Neuroticism. Regarding hand preference, 14 individuals were left-handed, seven were right-handed and seven were ambilateral. Contrary to our predictions, we did not find any relationship between personality scores and hand preference or sex. Instead, age was a significant predictor of personality scores, with older individuals being more agreeable and less extraverted. The link between brain lateralization and personality seems to be equivocal and dependent on personality and brain lateralization assessment methods. Further examinations of other proximate mechanisms, such as physiology or (epi)genetics, may elucidate what drives personality variation in common marmosets.